Static data flow analysis of PL/1 programs with the PROBE system - SARRAGA, R. F (IEEE transactions on software engineering, 1984)
PROBE is an experimental software system developed at the General Motors Research Laboratories for the analysis of PL/1 programs. It dissects their control flow structure and patterns of data use, thus pinpointing error-prone design and programming practices. An experimental data flow analyzer for PL/1 programs has been implemented within the PROBE system. A description is given of: 1. the data structures and algorithms used by the data flow analyzer, 2. the salient aspects of PL/1 usage in the analyzed production-level programs, and 3. the results of the data flow analysis. The simple design of PROBE shows how easily the user can analyze the most common uses of PL/1's block structure.